Perancangan Proyek Restoran Singapore dengan Pendalaman Biophilic Design oleh Konsultan Arsitektur Interior Epi Studio - Soesanto, Levia Nathalie; Rahadiyanti, Melania (KREASI, 2024)
With community life at the time of the pandemic entering the new normal, this opens up opportunities for architectural and interior consulting companies to create innovations that answer the needs of society. Many design trends carry the concepts of sustainability, user health, and nature, which are starting to become a trend during the current pandemic. This results from the need for a new normal that considers the impact of design on the user's health more. In addition, the issue of people's mental and physical health has become problematic because the pandemic's effects have had a significant influence on people's lifestyles and the economy. Epi Studio is here as an architectural and interior consultant that applies an approach to biophilic design in each project, to create a space or building design that can have a positive effect and help improve the quality of life of its users. To design eateries that can both attract customers and help users get closer to nature, Epi Studio collaborates with Singaporean eateries. Using the "Dine in Nature" concept, A Singaporean restaurant and coffee shop were designed using a biophilic approach. The design intended to give customers the impression that they were in a natural setting. This idea is implemented using 14 biophilic design patterns, including 3 patterns being prioritized as the primary means of resolving the site's current issues. It's intended that by implementing this idea, it will be possible to maximize comfort and positively affect its users while also providing guests with a feeling of a natural place.